SOSIO-CULTURAL ANALYSIS OF DIVORCE LEGISLATION A COMPARATIVE STUDY BETWEEN INDONESIA AND UNITED KINGDOM - Tri Astuti, Fakhriyah; Setiyawan bin Gunardi, Setiyawan; Erni Dewi Riyanti, Erni (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2023)
This study aims to compare the perspective of legal sources of divorce in Indonesia and the United Kingdom by using a  number of legal sources and other written literacy as the reading sources and reference (Public Research). This study used a qualitative-descriptive method by comparing divorce laws; analyzed the factors causing similarities and differences in the form of the rules in terms of divorce in Indonesia and the United Kingdom, and identified similarities and differences in how the two countries regulate the divorce issues. The researcher concerned with the biography and history of the two countries in the development of divorce law and found that social background, religion, political ideology, and history are the factors that have greatly affected the laws issued and implemented in country. This research will be a source of comparison and reflection for divorce law in Indonesia and the UK to become more progressive and developing. Alos, this research will be useful for further research on divorce law in Indonesia or the United Kingdom.   Keywords: Divorce Law, Indonesia, United Kingdom, Comparative.  Abstrak Studi ini adalah studi yang membandingkan perspektif sumber hukum perceraian di Indonesia dan Inggris. Dengan menggunakan sumber hukum dan literasi tertulis lainnya sebagai sumber bacaan dan acuan (Penelitian Pustaka). Penelitian ini menggunakan metode kualitatif-deskriptif, dengan membandingkan undang-undang perceraian serta menganalisa faktor-faktor yang menyebabkan persamaan dan perbedaan bentuk aturan-aturan mengenai perceraian di Indonesia dan United Kingdom, lalu menemukan persamaan dan perbedaan bagaimana kedua negara mengatur mengenai masalah perceraian. Dengan memperhatikan biografi dan sejarah kedua negara dalam perkembangan hukum perceraian. Penulis menemukan bahwa faktor latar belakang sosial, agama, ideologi politik, dan historis sangat mempengaruhi undang-undang yang disahkan dan diterapkan di suatu negara. Penelitian ini akan menjadi sumber perbandingan dan refleksi bagi hukum perceraian di Indonesia dan Inggris untuk menjadi lebih progresif dan berkembang, selain itu penelitian ini akan berguna bagi penelitian lanjutan mengenai hukum perceraian di Indonesia ataupun United Kingdom.